Platooning Strategy of Mobile Robot: Simulation and Experiment - Baarath, Kunjunni; Muhammad Aizzat, Zakaria; Suparmaniam, M. V.; Mohd Yazid, Abu (EDP Sciences, 2017)
Concurrent studies show vehicle platooning system as a promising approach for a new transportation system. The platooning strategy can be also applied to automated mobile robots. Including dynamic modelling in the simulation with kinematic model would yield a different result as the dynamic modelling would include the physical parameters of the mobile robot. The aim is to create a model that describes the motion of a robot that follows another robot based on predetermined distance. Dynamic model of the proposed mobile robot is simulated and the kinematic modelling was included in to simulate the motion of the mobile robot. PID controller will be used as a controller for robot’s motion and platooning strategy. A reference distance is given as the input and the PID controller computes the error and sends input to the mobile robot in the form of voltage. The robot is able to follow the leader robot by maintaining a distance of one metre with a small deviation in the direction as the robot tends to move towards the left due to forces acting on the wheel. This method can be implemented in a human following mobile robot where the leader robot is replaced with a human user.